1993
DOI: 10.1002/ptr.2650070405
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and adaptogenic properties of Momordica charantia extract: An experimental and clinical evaluation

Abstract: The hypoglycaemic properties of Mormodicu charuntiu (bitter gourd) water extract was tested on alloxan diabetic rats experimentally. A fall of blood sugar after 3 week's treatment with aqueous extract of fruits of the herb was found to be significant @<0.01). The aqueous extract of fruit was more effective in diabetes (fall of blood sugar 54% after 3 week's therapy) than the powder of the dried fruit (fall 25% nonsignificant). Hypoglycaemic effects in diabetic patients were found to be highly significant @<0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 17 publications
3
75
1
1
Order By: Relevance
“…In recent years, many traditional medicinal plants were tested for their antidiabetic potential in the experimental animals [16]. Although some of these plants have great reputation in the indigenous system of medicine for their antidiabetic activities, many remain to be scientifically established.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many traditional medicinal plants were tested for their antidiabetic potential in the experimental animals [16]. Although some of these plants have great reputation in the indigenous system of medicine for their antidiabetic activities, many remain to be scientifically established.…”
Section: Discussionmentioning
confidence: 99%
“…The most noteworthy health benefit of bitter gourd are the hypoglycemic potential demonstrated in normal [36] and diabetic [2,7,27,31] rats as well as in human subjects with type II diabetes mellitus [21] and its hypolipidemic effect [3,15,26,29]. The mechanism for the hypoglycemic effect of bitter gourd is still unclear, although it has been shown to inhibit glucose absorption [23], promote hepatic glucose utilization [31], possess an insulin-like polypeptide [18], and even to increase the insulin-positive cell number in the pancreas [1].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In a previous study, we reported that Momordica charantia decreased the blood glucose in genetically type 2 diabetic mice. An important type 2 diabetic cure is exercise therapy and diet.…”
mentioning
confidence: 99%